Influence of relative humidity on the electrical response of PEDOT:PSS based organic field-effect transistor - Zafar, Qayyum; Abdullah, Shahino Mah; Azmer, Mohamad Izzat; Najeeb, Mansoor Ani; Qadir, Karwan Wasman; Sulaiman, Khaulah (Elsevier, 2018)
We have investigated the influence of relative humidity on the electrical response of a bottom gate organic field-effect transistor (OFET) with poly(3,4-ethylenedioxythiophene)/poly(4-styrene sulfonate) (PEDOT:PSS) as an active channel material. For sensor fabrication, the organic polymer PEDOT:PSS has been spun-cast on highly doped n-Si wafer with preliminary thermally deposited gold, source and drain electrodes. The structural characterization and surface morphology study of active layer has been performed by XRD and FESEM, respectively. From the transfer characteristic curve, the p-type hole conductivity in PEDOT:PSS thin film is confirmed. Whereas from the output current-voltage (I–V) characteristic of the OFET, the Ion/Ioff ratio has been measured to be ∼2.6, when operated at relative humidity (RH) ∼60%. The humidity sensing characteristics of the OFET have further been investigated by exposing the proposed OFET to varied RH levels (40–80% RH) at room temperature (26.2 °C). Within the humidity range examined, the channel current has been observed to amplify by nearly 29.4 times of its magnitude.